METHODOLOGY FOR EXPERIMENTAL RESEARCH OF THE FIRE HAZARD OF POWER LITHIUM-ION BATTERIES OF ELECTRIC VEHICLES UNDER THE INFLUENCE OF A HEATING PANEL - Havryliuk, A. (Municipal economy of cities. Series: «Economy science», 2024)
Even though lithium-ion batteries (LIBs) are the subject of various tests and research at the production stage, there are no isolated cases of electric vehicle fires, and the development dynamics are unpredictable. The particular danger of such fires lies in the oxygen release during an irreversible exothermic reaction in LIBs, which creates new challenges for fire and rescue services when extinguishing such fires. The study aims to develop the main provisions of the methodology for experimental studies of electric vehicle power batteries in terms of fire hazards using an electric heating panel. The ultimate goal of the study is to determine the temperatures at which an irreversible exothermic reaction, the opening of ventilation holes, and the combustion (explosion) of electric vehicle power batteries begin, as well as the time parameters at which such processes occur. Taking into account the peculiarities of the occurrence and course of the irreversible exothermic reaction, we have developed a methodology, the essence of which is to determine the temperatures of the onset of the irreversible exothermic reaction of the electric vehicle power battery, the opening of ventilation holes, and the combustion (explosion) of electric vehicle power batteries, the combustion temperatures of ventilation gases, as well as the time parameters at which these processes occur, which may change during battery operation and not correspond to the declared parameters of the manufacturer. For this purpose, we exposed LIBs to thermal energy from an electric heating panel and recorded the temperature and time during which an irreversible exothermic reaction occurs from the moment of an internal short circuit to a fire or explosion. The use of the proposed methodology of experimental studies of the elements of power batteries of electric vehicles regarding the fire hazard of an electric heating panel will make it possible to determine the temperature limits of the occurrence of irreversible exothermic reactions in LIBs, as well as the time parameters under which these processes occur.